2019
DOI: 10.5093/rpadef2019e10
|View full text |Cite
|
Sign up to set email alerts
|

Creencias, actitudes y conductas de riesgo de entrenadores en relación con el peso de sus deportistas: un estudio descriptivo

Abstract: Este es un artículo Open Access bajo la licencia http://creativecommons.org/licenses/by-nc-nd/4.0/ Creencias, actitudes y conductas de riesgo de entrenadores en relación con el peso de sus deportistas: un estudio descriptivo RESUMEN: El entrenador/a es una de las principales figuras de referencia para el deportista y la presión que ejerza a través de sus propias actitudes y conductas puede ser uno de los factores más influyentes para desarrollar una alta preocupación por el peso y la figura. El objetivo del pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 19 publications
(38 reference statements)
1
5
0
Order By: Relevance
“…Pulkkinen (2001) [48] found that the main sources of information on weight loss promotion for professional female judo athletes were their coach (40%) and fellow or former female judo athletes (35%). According to Díaz (2020) [47], athletes trust coaches to modify weight, thus supporting the results obtained in this study. In addition, we added another idea that emerged regarding coaches, and it is that some are not able to identify disordered eating behaviors or even go as far as to encourage them.…”
Section: Role Of Reference Modelssupporting
confidence: 89%
See 4 more Smart Citations
“…Pulkkinen (2001) [48] found that the main sources of information on weight loss promotion for professional female judo athletes were their coach (40%) and fellow or former female judo athletes (35%). According to Díaz (2020) [47], athletes trust coaches to modify weight, thus supporting the results obtained in this study. In addition, we added another idea that emerged regarding coaches, and it is that some are not able to identify disordered eating behaviors or even go as far as to encourage them.…”
Section: Role Of Reference Modelssupporting
confidence: 89%
“…In the sports environment, it was mainly highlighted that the participants trusted the coaches, but the coaches were not able to identify disordered eating behaviors or even encouraged them [47]. Pulkkinen (2001) [48] found that the main sources of information on weight loss promotion for professional female judo athletes were their coach (40%) and fellow or former female judo athletes (35%).…”
Section: Role Of Reference Modelsmentioning
confidence: 99%
See 3 more Smart Citations